Laboratory rearing technique and biology of Mycotretus apicalis (Coleoptera: Erotylidae) on dried Pleurotus sajorcaju mushrooms - MOREIRA, GRAZIELLE F.; MOREIRA, CAMILA C.; ANDALÓ, VANESSA; MOINO JUNIOR, ALCIDES; CARDOSO-FREIRE, MARCELA M.; SOUZA-DIAS, EUSTÁQUIO (Revista Colombiana de Entomología, 2010)
Mycotretus apicalis is an erotylid beetle that is commonly found in cultivations Pleurotus sajor-caju in Minas Gerais, Brazil and could potentially be a pest. The life cycle is studied for the first time by laboratory rearing using dried P. sajor-caju mushrooms as both a feeding resource and an oviposition substrate. M. apicalis species has a generation time of about three weeks, with the egg-adult period was about 22 days, four larval instars, and the average longevity for adults of 89.7 ± 32.89 days. These results suggest that the M. apicalis has a potentially high rate of population increase, indicating its great potential to be a pest insect.